Effective Immunotherapy in Bone Marrow Metastatic Melanoma Presenting with Disseminated Intravascular Coagulopathy - Bolanle Gbadamosi; Daniel Ezekwudo; Bhadresh Nayak; Zhou Yu; Sandra Gjorgova-Gjeorgjievski; Ming Xie; Colvin Robert; Ishmael Jaiyesimi; Marianne Huben (Case Reports in Immunology)
Malignant melanoma is responsible for the majority of skin cancer deaths and is increasing in prevalence. Bone marrow (BM) involvement by melanoma is rare in the absence of widespread visceral disease. Here, we report the case of a 30-year-old female who presented to the hospital with back pain, low-grade fever, and easy bruising. She was found to be bicytopenic and in disseminated intravascular coagulopathy (DIC). Surprisingly, BM biopsy showed extensive involvement by metastatic malignant melanoma in the absence of visceral or brain metastasis. The unique presentation of this case and the challenge of management of a potentially treatable cancer in a critically ill patient are discussed, alongside a review of published cases of metastatic melanoma in the BM and an exploration of currently available treatment options. The excellent response of our patient to combined immune checkpoint inhibitors has yet to be paralleled in the available literature.